Indian Journal of Pharmaceutical Education and Research, Vol 60, Online First DOI: 10.5530/ijper.20260726 Copyright Information : Copyright Author (s) 2026 Distributed under Creative Commons CC-BY 4.0 Publishing Partner : Manuscript Technomedia. [www.mstechnomedia.com] A Validated HPTLC Method for Simultaneous Estimation of Berberine and Trigonelline in Polyherbal Mixture A Tool for Quality Control and Standardization - Patil, Sneha Basangouda; Jalalpure, Sunil Satyappa; Shetti, Priya Prakash (Indian Journal of Pharmaceutical Education and Research, 2026)
Introduction: Berberis aristata and Trigonella foenumgrecum have been used in traditional medicine for various purposes due to their diverse therapeutic benefits such as anti-inflammatory, antidiabetic, antihypertensive and digestive properties. Berberis aristata and Trigonella foenumgrecum consists of bioactive markers Berberine and Trigonelline respectively. Aim: This study aimed to develop a simple, rapid reliable and robust HPTLC method for the simultaneous quantification of biomarkers in polyherbal mixture. Materials and Methods: The separation of these active compounds from the polyherbal mixture was achieved using a mobile phase consisting of toluene: ethyl acetate: formic acid: methanol (6:3:0.3:1v/v/v/v) on pre-coated Silica G 60 F254 plates. Validation of the method encompassed assessments of linearity, accuracy, precision, limits of detection and quantification, robustness and specificity. Results: Berberine and Trigonelline displayed distinct Rf values of 0.88 and 0.29 respectively. The method demonstrated excellent linearity across the concentration range of 2-10 μg/band, with correlation coefficients of 0.9966 and 0.9973 for Berberine and Trigonelline respectively. Conclusion: Percentage recovery was found within the range of 98.84-102.92%. The proposed HPTLC method can be implemented for the concurrent estimation of Berberine and Trigonelline for routine quality control of herbal formulations containing these herbs.
Keywords: Berberine; Trigonelline; Polyherbal mixture; HPTLC; Analytical method validation; Quality control.